2023
DOI: 10.3390/diagnostics13010153
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Bladder Involvement in the Outcome of Upper Tract Urothelial Carcinoma

Abstract: Accurately predicting the clinical prognosis of upper tract urothelial carcinoma (UTUC) seems crucial. We evaluated the effect of the involvement of urothelial bladder carcinoma (UBC) as a potential prognostic factor for overall survival (OS) and progression-free survival (PFS). The cohort included 115 patients with UTUC, subgrouped between January 2009 and December 2019 as follows: (1) only UTUC and (2) UTUC with synchronous or metachronous UBC (UTUC + UBC). Univariate and multivariate analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…LVI was found to be a significant predictor of disease recurrence (pooled HR: 1.43, 95% CI: 1.31-1.55, p = 0.000; I(2) = 76.3%), CSS (pooled HR: 1.53, 95% CI: 1.41-1.66, p = 0.000; I(2) = 72.3%), and OSS (HR: 1.56, 95% CI 1.45-1.69, p = 0.000; I(2) = 62.9%) [93]. Another study indicated an association between LVI and OS (HR 4.980 CI 95%1.763-14.064, p = 0.002), and PFS (HR 2.687 CI 95%1.172-6.163, p = 0.020) [94].…”
Section: Lymphovascular Invasionmentioning
confidence: 97%
See 1 more Smart Citation
“…LVI was found to be a significant predictor of disease recurrence (pooled HR: 1.43, 95% CI: 1.31-1.55, p = 0.000; I(2) = 76.3%), CSS (pooled HR: 1.53, 95% CI: 1.41-1.66, p = 0.000; I(2) = 72.3%), and OSS (HR: 1.56, 95% CI 1.45-1.69, p = 0.000; I(2) = 62.9%) [93]. Another study indicated an association between LVI and OS (HR 4.980 CI 95%1.763-14.064, p = 0.002), and PFS (HR 2.687 CI 95%1.172-6.163, p = 0.020) [94].…”
Section: Lymphovascular Invasionmentioning
confidence: 97%
“…Concomitant carcinoma in situ is associated with worse CSS and RFS (HR: 1.25; p = 0.004, and HR: 1.24; p = 0.006, respectively) [105]. Urothelial bladder cancer occurring at the same time (synchronous) or a different time (metachronous) with UTUC is a predictor of worse PFS (HR: 3.326 CI 95% 1.474-7.503, p = 0.004), but not OS [94].…”
Section: Other Factorsmentioning
confidence: 99%